SEMUT (TENSES VERB MUTER) AS A MEDIA TO UNDERSTAND BASIC ENGLISH (TENSES AND VERB) FOR STUDENTS IN PLUMPANG TUBAN 1 MIDDLE STATE - Tyas Rahayu Kartika; Ratna Rahayu Nengseh; Nur Lujeng Kinanti; Eni Indria Safitri; Albrian Fiky Prakoso (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2020)
This study aims to determine the results of the development of the media SEMUT (Verb Muter Tenses) with a series of learning media ERTE MAP (Preparation of Verb Words and Tenses) and a module entitled "Learn Basic English (Tenses and Verb): Simple Present Tense, Simple Past Tense, Present Continuous Tense "that is to improve the English language skills of students and know students' responses to the use of the media. The research method used was one group pre-test post-test design. This method is carried out by giving students pre-test and post-test questions, as a qualitative method is carried out by interviewing several students who have participated in the implementation of the SEMUT Learning Media program (Verb Muter Tenses). The pre-test and post-test were distributed to 31 students of Plumpang 1 Public High School, Tuban to find out the values before and after the implementation of the SEMUT media. Meanwhile, the interview was conducted to determine the students' interest of SEMUT media.